LoRaWAN Performance evaluation - Figueiredo, Tiago Afonso Antunes de (2019)
The Internet of Things (IoT) is expected to grow in the upcoming years. LoRaWAN is one promising Low Power Wide Area Network (LPWAN) standard proposed for IoT widely adopted across the world. It runs on unlicensed spectrum and was designed to carry sporadic traffic. This dissertation analyses the performance of LoRaWAN in extreme conditions, where peak traffic loads occur in the network. It starts by evaluating the Network Simulator 3 (ns- 3) LoRaWAN module, identifying and correcting their implementation. In a second phase, it evaluates the limitations of the class A LoRaWAN access protocol during synchronized peaks of traffic, and proposes a new access algorithm to improve the reliability and reduce the latency.